Dreams That Glitter - Girls Aloud (Musical group) (London Bantam Press, 2008)
The autobiography and style guide of the most successful girl group the UK has ever seen.
Include Color Illustration and Index
Keywords: Great Britain -- Girls Aloud (Musical group) -- Rock musicians